Estrutura de prática e nível de desenvolvimento motor na aprendizagem da habilidade especializada - Cicero Luciano Alves Costa (2015)
The aim of the present study was to investigate the relations between the level of motor development and practice schedule on the learning of a specialized motor skill. The sample was composed by 38 children, from 9 to 10 years old. The level of motor development on throwing and smash was analyzed. The classification of fundamentals motor skill pattern was done by the Instrumental of fundamental movements Evaluation proposed by McClenanghan and Gallahue (1985) by recording participants executions. The learned sport motor skill during experimental phase was the volleyball tennis serve, adapted from Ugrinowitsch and Manoel (1999). There were four experimental groups: constant-random mature group - GMCA, constant-random non-mature group - GNMCA; random mature group - GMA, and random non-mature group - GNMA). The study consisted of two stages. First, the selection phase of the participants based on criteria related to motor development level. Second, an intervention composed of pretest, acquisition, intermediate test and retention. All the four tests had 12 trials and acquisition phase had 210 trials divided on 10 practice sessions. The task variations from random practice occurred in relation to the different regions of serving and performance was analyzed through the movement pattern and the accuracy in the target. The inferential analysis was done by three-way ANOVA with repeated measures and post hoc LSD for pair comparison, in addition to the Spearman correlation test. Children with mature pattern on fundamental motor skills showed significant improvement on movement pattern after the experiment, which is outperformed children without mature patterns in the retention test. In relation to performance, only the GMCA showed significant improvement. There were correlation between the components of the fundamental motor skills and serve performance in retention test. The similarity in motor development levels in GMCA and GMA groups ensured equal the effectiveness of the practice schedule only in the analysis of movement patterns, showing to be required to considerate the level of development in order to maximize the effect of the practice schedule. Allied to this result, the lack of performance improvement of non-mature group supports the hypothesis of proficiency barrier raised by Seefeldt (1979), which highlights the importance of mature patterns of fundamental motor skills for the development of specialized motor skills.